Man in the music : the creative life and work of Michael Jackson - Vogel, Joseph, 1981- (New York : Sterling, 2011)
Analyzes every song and album of Jackson's solo career, from 1979's groundbreaking "Off the Wall" to his yet-to-be released material, placing the music in its social, historical, and cultural context.
Off the wall -- Thriller -- Bad -- Dangerous -- History : past, present, and future, book 1 -- Blood on the dance floor : history in the mix -- Invincible -- The final years -- Michael.
Includes bibliographical references (p. 270-294) and index.
Keywords: Jackson, Michael, -- 1958-2009 -- Criticism and interpretation; Popular music -- United States -- History and criticism